1979
DOI: 10.1007/bf00215364
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of cell proliferation by calcium and cyclic AMP

Abstract: Calcium, in partnership with cyclic AMP, controls the proliferation of non-tumorigenic cells in vitro and in vivo. While it does not seem to be involved in the proliferative activation of cells such as hepatocytes (in vivo) or small lymphocytes (in vitro), it does control two later stages of prereplicative (G1) development. It must be one of the very many regulatory and permissive factors affecting early prereplicative development, because severe calcium deprivation reversibly arrests some types of cell early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
78
2
2

Year Published

1982
1982
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(83 citation statements)
references
References 105 publications
1
78
2
2
Order By: Relevance
“…Therefore an indirect mechanism via the increase in cyclic AMP caused by PTH in osteoblasts [26] has been considered to lead to bone resorption [27]. PTH also caused, by a cyclic AMPindependent mechanism [28] involving a Ca2+/phosphoinositide pathway [20,29,30], increased cell proliferation in rat osteoblasts and increased DNA synthesis in chicken osteoblasts and chondroblasts [31][32][33], and in rat calvaria [20]. Moreover, we found Thr for Leu-37, or the substitution of Met for Phe-34 alone, produced 100 %-resistant fragments.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore an indirect mechanism via the increase in cyclic AMP caused by PTH in osteoblasts [26] has been considered to lead to bone resorption [27]. PTH also caused, by a cyclic AMPindependent mechanism [28] involving a Ca2+/phosphoinositide pathway [20,29,30], increased cell proliferation in rat osteoblasts and increased DNA synthesis in chicken osteoblasts and chondroblasts [31][32][33], and in rat calvaria [20]. Moreover, we found Thr for Leu-37, or the substitution of Met for Phe-34 alone, produced 100 %-resistant fragments.…”
Section: Introductionmentioning
confidence: 99%
“…PTH also causes increased proliferation of thymus, bone marrow and liver in vivo [18], increases which are mediated by changes in Ca2l and/or cyclic AMP concentrations, in a variety of cell culture systems [8,17]. As well as increasing adenylate cyclase activity [19], PTH increases the proliferation [13,14] of cultured bone cells, osteosarcoma cells and chondroprogenitor cells [20].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary and lifestyle factors may have an important role in the development of breast cancer (2)(3)(4) , among which Ca intake has been suggested as a potential protective factor in mounting experimental research (5)(6)(7)(8)(9)(10) and several observational studies (11)(12)(13) . A metaanalysis by Chen et al (14) involving six prospective cohorts and nine case-control studies suggested a significant inverse association between Ca intake and risk of breast cancer, with a summary relative risk (RR) of 0·81 (95 % CI 0·72, 0·90) for the highest compared with the lowest intake of Ca, with a significant publication bias.…”
mentioning
confidence: 99%